Microsoft Windows Home Server unleashed - McFedries, Paul (Unleashed., 2010)
Microsoft® Windows® Home Server Unleashed Second Edition Covers PowerPacks 1, 2, and 3! Paul McFedries This is the most comprehensive, practical, and useful guide to Windows Home Server, including Microsoft's major updates in PowerPacks 1, 2, and 3. Top Windows expert Paul McFedries brings together tips, techniques, and shortcuts available nowhere else and presents them all in plain English for every Windows Home Server user. McFedries covers all facets of running Windows Home Server: configuration, file/folder sharing, networking, media streaming and sharing, backup/restore, monitoring, Web and SharePoint site deployment, performance optimization, maintenance, and customization. He thoroughly addresses Windows Home Server's new Windows 7 support, as well as major improvements in areas ranging from remote access to storing TV recordings. This edition presents comprehensive, up-to-the-minute guidance on Windows Home Server security, plus a full section of advanced solutions utilizing Microsoft's power tools, the command line, and automated scripting. Throughout, McFedries demonstrates key techniques through real-world examples and presents practical configurations you can easily use in your own home. Detailed information on how to… Set up Windows Home Server networks, user accounts, devices, and storage Integrate with Windows 7's new file libraries, backup/recovery tools, and Windows Search 4.0 Efficiently share folders, files, and digital media Ensure security for both local and remote users Automatically back up and restore all the computers on your home network Quickly set up web and SharePoint sites Tune, maintain, and troubleshoot Windows Home Server Use the new Remote Access Configuration and Repair Wizards ON THE WEB: Register your book at informit.com/title/9780672331060 to access all examples and source code presented in this book. Category: Windows Server Covers: Windows Home Server with PowerPacks 1, 2, 3 User Level: Intermediate–Advanced.